Community-Based Occupational Health Promotion for Rural Youth Through Ergonomic Education and Therapeutic Swimming Training - Miftachul A'la; Agung Nugroho; Warsiyah; Kofi Ampomah Kabenefo (Dimas: Jurnal Pemikiran Agama untuk Pemberdayaan, 2025)
Occupational health issues in rural informal industries, particularly home-based garment production, are often overlooked despite the high risk of musculoskeletal disorders among young workers. This community service program aimed to improve occupational health literacy and physical well-being among rural youth through ergonomic education and therapeutic swimming training in Ngadirejo Village, Boyolali. Implemented in collaboration with Karang Taruna “Gambate,” the program applied a community-based participatory approach over eight months. Interventions included ergonomic training on proper posture, simple workstation adjustments, micro-break and stretching routines, and therapeutic swimming to support muscle recovery. A one-group pre-test and post-test design using the Occupational Health Knowledge Scale and the Nordic Musculoskeletal Questionnaire was used for evaluation. Results showed a 28.8% increase in ergonomic knowledge and a 23.5% decrease in musculoskeletal complaints. In conclusion, participatory and low-cost ergonomic interventions effectively improved health awareness, reduced physical strain, and strengthened productive behavior among rural youth workers.